User's guide to Sears list of subject headings - Satija, Mohinder Partap 1949- (Lanham, Maryland Rowman & Littlefield, 2020)
Covers "the importance of vocabulary control, the process of subject analysis, the structure and organization of the Sears List, and the methods to locate, specify, and construct subject headings and provide cross references for the public catalog."--Back cover.
Part I. An Introduction to Controlled Vocabulary of the Sears List. Controlled Vocabularies -- Minnie Earl Sears: A Career Sketch -- History and Chronology of the Sears List of Subject Headings -- About the twenty-second edition of the Sears List -- Part II. Working with the Sears List. Structure of the Sears List -- Subject Analysis -- Principles of the Sears List -- Key Headings -- Headings Omitted in the Sears List -- Subdivisions -- Cross References -- Geographical Headings and Subdivisions -- Subject Headings for Languages and Linguistics -- Subject Headings for Literature and Literary Works -- Subject Headings for Biographies and Autobiographies -- Working with the Online Sears -- Sears List of Subject Headings and MARC Coding -- Publications Not Requiring Subject Headings -- Answers to the Review Questions and Exercises.
Includes bibliographical references (pages 203-211) and index.
Keywords: Subject cataloging -- Handbooks, manuals, etc; Subject cataloging; Subject headings; Handbooks and manuals